Cerebrospinal fluid and plasma concentration of soluble intercellular adhesion molecule1, vascular cell adhesion molecule1 and endothelial leukocyte adhesion molecule in patients with acute ischemic b - Selaković Vesna M.; Čolić Miodrag J.; Jovanović Marina D.; Raičević Ranko; Jovičić Aco (Vojnosanitetski Pregled)
Background. Leukocyte migration into the ischemic area is a complex process controlled by adhesion molecules (AM) in leukocytes and endothelium, by migratory capacity of leukocytes and the presence of hemotaxic agents in the tissue. In this research it was supposed that in the blood and cerebrospinal fluid (CSF) of patients in the acute phase of ischemic brain disease (IBD) there were relevant changes in the concentration of soluble AM (sICAM-1 sVCAM-1 and sE-selectin), that could have been the indicators of the intensity of damaging processes in central nervous system (CNS). Methods. The study included 45 IBD patients, 15 with transient ischemic attack (TIA) 15 with reversible ischemic attack (RIA), and 15 with brain infarction (BI) of both sexes, mean age 66±7. Control group consisted of 15 patients with radicular lesions of discal origin, subjected to diagnostic radiculography without the signs of interruption in the passage of CSF. Changes of selected biochemical parameters were determined in all patients in frame 72 hours since the occurence of an ischemic episode. Concentrations of soluble AM were determined in plasma and CSF by ELISA. Total number of leukocytes (TNL) in peripheral blood was determined by hematological analyzer. Results. The results showed that during the first 72 hrs of IBD significant increases occured in TNL and that the increase was progressive compared to the severeness of the disease. Significant increase of soluble AM concentration was shown in plasma of IBD patients. The increase was highest in BI somewhat lower in RIA and the lowest in TIA patients compared to the control. In CSF concentrations of sICAM-1, sVCAM-1 and sE-selectin demonstrated similar increasing trend as in plasma. Conclusion. TNL, as well as the soluble AM concentrations in plasma and CSF, were increased during the acute IBD phase and progressive in relation to the severeness of the disease, so that they might have been the indicators of CNS inflammatory reaction intensity. Furthermore, the results indicated their role in IBD pathogenesis and offered the possibility of researching the application of antagonists and/or activity modulators of some of them in IBD therapy.